Extended Two Phase Commit Protocal In Real Time Distributed Database System (International Journal of Engineering and Computer Science, 2015)
The two phase commit (2pc) protocol is widely used for commit processing in distributed data base system (DDBSs). The blocking problem in 2pc reduces the availability of the system as the blocked transaction keeps all the resources until receive the final command from the coordinator after its recovery. To remove the blocking in 2pc, three phase commit (3pc) protocol was proposed. Although 3pc protocol eliminates the blocking problem, it involves an extra round of message transmission, which degrades system performance in DDBSs. Both 2pc and 3pc having problem which degrades system efficiency .In order to remove this problem in 2pc and 3pc ,E2PCP protocol was introduce to enhance system performances as compare to 2pc and 3pc.To reduce blocking, we propose an extended two phase commit protocol (E2PCP) by attaching multiple participant sites to the coordinator sites work as a backup sites or as substitute sites for coordinator sites. In this protocol, after receiving responses from all participant sites in the first phase, the coordinator communicates the final decision to the backup sites in the back phase. Afterward, it send final decision to the participants. When blocking occur due to failure of coordinator site, the participant site can terminate the transaction by consulting backup sites of the coordinator. In this way E2PCP protocol achieving non-blocking in most of coordinator sites failures.